Experimental and Numerical Analysis of Dynamic Properties of Wound and Wrapped Carbon Composites - Kulhavy, Petr; Fliegel, Vitezslav (Manufacturing Technology Journal, 2019)
In the presented work, static and dynamic properties of two, theoretically identical composite rods were studied. Those two kinds of rod were made of pre-impregnated fibers so called "prepregs". The first of them was made by means of wrapping technology, which is simply just helical layering of one wide tape around a rotating mandrel. The weakness of this method is possible using only for straight parts. That is why a simultaneous deposition of several thinner filaments in a form of tape called winding was used in order to optimize this technology also for curved parts with various cross-sections.The target of this work was to compile numerical model and experimentally compare flexural strength of the theoretically identical wrapped and wound rods in the static three point test.Further small samples cut and extracted from those rods were subjected to dynamic bending loading on Dynamic Mechanical Analyzer, with various loading speed, in order to obtain also the dynamic properties. The found results and conclusions of this article should provide a basic idea how significantly the manufacturing process could affects the microstructure and real mechanical properties of long fibers composite parts.
Keywords: Carbon Composites; Bending Test; DMA; Winding; Wrapping